Crosslinking agent for rubber and preparation method

By using a crosslinking agent containing polystyrene microspheres and copper sulfate in nitrile rubber to form a mesh crosslinking structure, the problems of poor chemical stability and low crosslinking efficiency of crosslinking agents in the prior art are solved, efficient vulcanization and mechanical properties are improved, and the self-healing ability of the material is improved.

CN119552471APending Publication Date: 2025-03-04DONGYING XILIN ENVIRONMENTAL PROTECTION TECH CO LTD

Patent Information

Application Number
CN202411805857.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-10
Publication Date
2025-03-04

AI Technical Summary

Technical Problem

In the prior art, the crosslinking agent of nitrile rubber has poor chemical stability, is inconvenient to use, and has low crosslinking efficiency, which affects mechanical properties and toughness.

Method used

A crosslinking agent for rubber is used, and its raw materials include polystyrene microspheres, methyl orthosilicate, copper sulfate, surfactant, etc., and a hollow microsphere structure is formed by compounding and deposition, ethyleneization and bonding with vinyl acetate to provide a coordination crosslinking point, and a network crosslinking structure is formed by coordination between transition metal and rare earth.

Benefits of technology

It realizes efficient vulcanization of nitrile rubber, improves mechanical properties and toughness, reduces metal salt content and cost, and the system has multiple network structures of reversible coordination bonds and non-covalent bonds, improving self-healing capabilities.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119552471A_ABST
    Figure CN119552471A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of rubber additives, in particular to a cross-linking agent for rubber and a preparation method. The cross-linking agent for rubber is prepared from the following raw materials in parts by mass: 5 to 10 parts of polystyrene microspheres, 1 to 5 parts of tetramethyl orthosilicate, 0.1 to 0.5 part of copper sulfate, 1 to 2 parts of a surfactant, 1 to 2 parts of vinyl trimethoxy silane, 0.01 to 0.1 part of an initiator, 2 to 6 parts of vinyl acetate, 1 to 2 parts of cobalt acetate, 0.01 to 0.1 part of yttrium chloride and 1 to 2 parts of graphene oxide. Transition metal salt and rare earth are compounded and loaded on the surface of grafted silicon dioxide, the specific surface area of the metal salt can be effectively increased, the coordination efficiency is improved, the adding amount of the metal salt is reduced, meanwhile, self-repairing of crosslinking and reinforcing functions can be effectively achieved, and the crosslinking agent is high in stability and has higher environmental tolerance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of rubber additives, and in particular to a cross-linking agent for rubber and a preparation method thereof. Background Art

[0002] Cross-linking agents play an important role in enhancing the performance of rubber. Cross-linking through covalent bonds is the main method of rubber cross-linking, which has the advantage of structural stability. However, due to the stability and irreversibility of covalent bonds, vulcanized rubber is difficult to recycle.

[0003] Nitrile rubber is a new type of highly saturated rubber. Its traditional crosslinking agent is organic peroxide, which not only has poor chemical stability and is inconvenient to use, but also uses covalent bonds as its crosslinking bond. However, when it is filled with an acidic reinforcing agent, the crosslinking efficiency is sometimes reduced due to the decomposition of peroxide ions, and the mechanical properties are significantly reduced. Compared with covalently crosslinked nitrile rubber, non-covalently crosslinked rubber has better reversibility. Even if the modulus of the system is not reinforced with carbon black, it can be significantly improved, but the crosslinking effect and toughness of the system are not ideal.

[0004] CN102504294B discloses a method for preparing a cerium sulfate coordinated cross-linked nitrile elastomer, which has the advantages of less use of a coordination cross-linking agent (cerium sulfate), high vulcanization efficiency, and simple process, and meets the requirements for the development of green vulcanization. However, when encountering water, the metal salt particles can be dissolved and extracted by water, which has a great impact on the material properties.

[0005] CN101486800B discloses a method for cross-linking nitrile rubber by loaded transition metal, which realizes cross-linking by coordinating transition metal salt with nitrile group in nitrile rubber, and its mechanical properties are obviously better than the existing vulcanized reinforced nitrile rubber, and its oil resistance is more excellent. However, its coordination efficiency is relatively low, and a large amount of metal salt needs to be added to achieve a good cross-linking effect. Summary of the invention

[0006] The purpose of the present invention is to solve the shortcomings of the prior art and to propose a cross-linking agent for rubber and a preparation method thereof.

[0007] A crosslinking agent for rubber, whose raw materials include, by mass, 5-10 parts of polystyrene microspheres, 1-5 parts of methyl orthosilicate, 0.1-0.5 parts of copper sulfate, 1-2 parts of surfactant, 1-2 parts of vinyltrimethoxysilane, 0.01-0.1 parts of initiator, 2-6 parts of vinyl acetate, 1-2 parts of cobalt acetate, 0.01-0.1 parts of yttrium chloride and 1-2 parts of graphene oxide.

[0008] Preferably, the surfactant is Span-20.

[0009] Preferably, the initiator is dibenzoyl peroxide.

[0010] The preparation method of the above-mentioned rubber cross-linking agent comprises the following steps:

[0011] S1. Add polystyrene microspheres, methyl orthosilicate and copper sulfate into water and stir for 10-20 min, add petroleum ether and surfactant and stir for 5-10 min, adjust the pH value of the system to 8-9, perform ultrasonic treatment for 1-2 h, centrifuge, wash, calcine at 400-500° C. for 10-30 min, cool to room temperature, add toluene and mix well to obtain activated silica;

[0012] S2, adding vinyl trimethoxysilane to water and stirring for 10-30 minutes, adding activated silica, condensing and refluxing at 80-90°C under nitrogen protection for 5-10 hours, adding initiator and stirring for 5-20 minutes, adding vinyl acetate and continuing to reflux for 10-20 hours, centrifuging, washing, and vacuum drying to obtain grafted silica;

[0013] S3. Add the grafted silica to deionized water, add cobalt acetate, yttrium chloride and graphene oxide, and ultrasonically treat for 1-2 hours, filter, wash and vacuum dry.

[0014] Preferably, in S1, the ultrasonic frequency is 10-14 kHz.

[0015] Preferably, in S1, the centrifugal speed is 4000-5000 rpm, and the centrifugal time is 2-5 min.

[0016] Preferably, in S3, the ultrasonic frequency is 5-12 kHz, and the ultrasonic temperature is 50-70°C.

[0017] Preferably, in S3, the vacuum drying temperature is 50-60°C.

[0018] The method for using the above-mentioned rubber crosslinking agent comprises the following steps: mixing nitrile rubber, the above-mentioned rubber crosslinking agent and an antioxidant into sheets, hot pressing and vulcanizing at 150-160°C, the hot pressing time is 15-25 minutes, and the hot pressing pressure is 12-16MPa.

[0019] Preferably, the mass ratio of the nitrile rubber, the rubber cross-linking agent according to any one of claims 1 to 3, and the antioxidant is 100:1-3:2-4.

[0020] Beneficial effects:

[0021] The present invention utilizes methyl orthosilicate and copper sulfate to compound and deposit on the surface of polystyrene microspheres, and after calcination, vinylizes the surface of the formed hollow microsphere structure, and then combines with vinyl acetate, which can not only achieve good blending effect with nitrile rubber, but also utilize the organic layer and graphene oxide therein to provide coordination crosslinking points, and then the coordination of transition metal and rare earth effectively promotes the formation of coordination crosslinking between chain rubber molecules, promotes the rubber molecular structure to change from a chain structure to a network crosslinking structure, and effectively realizes the vulcanization of nitrile rubber. At the same time, the obtained vulcanized rubber has good mechanical properties, and the system maintains good toughness.

[0022] The present invention loads transition metals and rare earths on the surface of reinforcing materials, which not only makes the transition metals more evenly distributed, but also greatly increases the specific surface area of ​​the transition metals. When used in the hot-pressing vulcanization forming process of nitrile rubber, coordination bonds can be formed to effectively realize the coordination crosslinking of the nitrile rubber. Moreover, compared with traditional rubber, the present invention not only significantly increases the coordination efficiency, reduces the required metal salt content, and reduces the cost, but also cooperates with the reversible coordination bonds therein, and the system has a multiple network structure of reversible covalent bonds and non-covalent bonds, which can effectively realize the self-repair of crosslinking and reinforcing functions, comprehensively improve the self-repair ability of the nitrile rubber, and at the same time, the repair process is simple and the repair efficiency is high, so the nitrile rubber is suitable for use as a new functional material.

[0023] The present invention proposes a new cross-linking method for nitrile rubber, which not only has high chemical stability and is easy to use and store, but also has strong interface interaction between the cross-linking agent and the nitrile rubber matrix. The obtained vulcanized rubber has good mechanical properties, indicating that the toughness of the system is better maintained. The cross-linked nitrile rubber of the present invention is reversible during the stretching process and has a good self-repairing effect.

[0024] The process of the present invention is simpler, safer, and convenient to operate, and is suitable for large-scale industrial production; at the same time, the cross-linking agent has high stability and higher environmental tolerance. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 This is a scanning electron microscope image of the rubber cross-linking agent obtained in Example 5.

[0026] Figure 2 The stress-strain curves of the vulcanized nitrile rubber obtained in Example 5 and Comparative Examples 1-4 are shown.

[0027] Figure 3 It is a comparison chart of the crosslinking density of the vulcanized nitrile rubber obtained in Example 5 and Comparative Examples 1-4.

[0028] Figure 4 It is a comparison chart of the tensile strength recovery rate of the vulcanized nitrile rubber obtained in Example 5 and Comparative Examples 1-4. DETAILED DESCRIPTION

[0029] The present invention will be further explained below in conjunction with specific embodiments.

[0030] Example 1

[0031] A cross-linking agent for rubber, whose raw materials include: 5g of polystyrene microspheres, 1g of methyl orthosilicate, 0.1g of copper sulfate, 1g of Span-20, 1g of vinyltrimethoxysilane, 0.01g of dibenzoyl peroxide, 2g of vinyl acetate, 1g of cobalt acetate, 0.01g of yttrium chloride and 1g of graphene oxide.

[0032] The preparation method of the above-mentioned rubber cross-linking agent comprises the following steps:

[0033] S1. Add polystyrene microspheres, methyl orthosilicate and copper sulfate to 50 g of water, stir at 500 r / min for 10 min, add 200 g of petroleum ether and Span-20, stir at 5000 r / min for 5 min, adjust the pH value of the system to 8-9, perform ultrasonic treatment for 1 h, the ultrasonic frequency is 10 kHz, centrifuge at 4000 rpm for 2 min, wash, calcine at 400 ° C for 10 min, cool to room temperature, add 100 g of toluene and mix well to obtain activated silica;

[0034] S2, adding vinyl trimethoxysilane to 5 g of deionized water and stirring for 10 min, adding activated silica, condensing and refluxing at 80° C. for 5 h under nitrogen protection, adding dibenzoyl peroxide and stirring for 5 min, adding vinyl acetate, continuing to reflux for 10 h, centrifuging, washing, and vacuum drying to obtain grafted silica;

[0035] S3. Add the grafted silica to 8 g of deionized water, add cobalt acetate, yttrium chloride, and graphene oxide, and perform ultrasonic treatment for 1 h at an ultrasonic frequency of 5 kHz and an ultrasonic temperature of 50° C., filter, wash, and dry in a vacuum at 50° C.

[0036] The method for using the above-mentioned rubber crosslinking agent comprises the following steps: feeding nitrile rubber, rubber crosslinking agent and antioxidant into a double-roll mixer at a mass ratio of 100:1:2 to mix into sheets, wherein the mixing temperature is 90°C and the mixing time is 10 minutes; and then feeding into a flat-plate vulcanizer for hot pressing vulcanization molding, wherein the hot pressing temperature is 150°C, the hot pressing time is 15 minutes, and the hot pressing pressure is 12MPa.

[0037] Example 2

[0038] A cross-linking agent for rubber, whose raw materials include: 10g of polystyrene microspheres, 5g of methyl orthosilicate, 0.5g of copper sulfate, 2g of Span-20, 2g of vinyltrimethoxysilane, 0.1g of dibenzoyl peroxide, 6g of vinyl acetate, 2g of cobalt acetate, 0.1g of yttrium chloride and 2g of graphene oxide.

[0039] The preparation method of the above-mentioned rubber cross-linking agent comprises the following steps:

[0040] S1. Add polystyrene microspheres, methyl orthosilicate and copper sulfate to 100 g of water, stir at 1000 r / min for 20 min, add 300 g of petroleum ether and Span-20, stir at 10000 r / min for 10 min, adjust the pH value of the system to 8-9, perform ultrasonic treatment for 2 h, the ultrasonic frequency is 14 kHz, centrifuge at 5000 rpm for 5 min, wash, calcine at 500 ° C for 30 min, cool to room temperature, add 150 g of toluene and mix well to obtain activated silica;

[0041] S2, adding vinyl trimethoxysilane to 10g of deionized water and stirring for 30min, adding activated silica, condensing and refluxing at 90°C for 10h under nitrogen protection, adding dibenzoyl peroxide and stirring for 20min, adding vinyl acetate, continuing to reflux for 20h, centrifuging, washing, and vacuum drying to obtain grafted silica;

[0042] S3. Add the grafted silica to 16 g of deionized water, add cobalt acetate, yttrium chloride, and graphene oxide, and ultrasonically treat for 2 h at an ultrasonic frequency of 12 kHz and an ultrasonic temperature of 70°C. Filter, wash, and vacuum dry at 60°C.

[0043] The method for using the above-mentioned rubber crosslinking agent comprises the following steps: feeding nitrile rubber, rubber crosslinking agent and antioxidant into a double-roll mixer at a mass ratio of 100:3:4 to mix into sheets, wherein the mixing temperature is 95°C and the mixing time is 20 minutes; and then feeding into a flat-plate vulcanizer for hot pressing vulcanization molding, wherein the hot pressing temperature is 160°C, the hot pressing time is 25 minutes, and the hot pressing pressure is 16MPa.

[0044] Example 3

[0045] A cross-linking agent for rubber, whose raw materials include: 7g of polystyrene microspheres, 4g of methyl orthosilicate, 0.2g of copper sulfate, 1.7g of Span-20, 1.2g of vinyltrimethoxysilane, 0.07g of dibenzoyl peroxide, 3g of vinyl acetate, 1.7g of cobalt acetate, 0.02g of yttrium chloride, and 1.8g of graphene oxide.

[0046] The preparation method of the above-mentioned rubber cross-linking agent comprises the following steps:

[0047] S1. Add polystyrene microspheres, methyl orthosilicate and copper sulfate to 70 g of water, stir at 900 r / min for 12 min, add 280 g of petroleum ether and Span-20, stir at 7000 r / min for 9 min, adjust the pH value of the system to 8-9, perform ultrasonic treatment for 80 min, the ultrasonic frequency is 13 kHz, centrifuge at 4200 rpm for 4 min, wash, calcine at 420 ° C for 25 min, cool to room temperature, add 110 g of toluene and mix well to obtain activated silica;

[0048] S2, adding vinyl trimethoxysilane to 9 g of deionized water and stirring for 15 min, adding activated silica, condensing and refluxing at 88 ° C for 7 h under nitrogen protection, adding dibenzoyl peroxide and stirring for 16 min, adding vinyl acetate, continuing to reflux for 12 h, centrifuging, washing, and vacuum drying to obtain grafted silica;

[0049] S3. Add the grafted silica to 14 g of deionized water, add cobalt acetate, yttrium chloride, and graphene oxide, and perform ultrasonic treatment for 80 min at an ultrasonic frequency of 10 kHz and an ultrasonic temperature of 55° C., filter, wash, and vacuum dry at 52° C.

[0050] The method for using the above-mentioned rubber crosslinking agent comprises the following steps: feeding nitrile rubber, rubber crosslinking agent and antioxidant into a double-roll mixer at a mass ratio of 100:2.5:2.5 to mix into sheets, wherein the mixing temperature is 93°C and the mixing time is 12 minutes; and then feeding into a flat-plate vulcanizer for hot pressing vulcanization molding, wherein the hot pressing temperature is 158°C, the hot pressing time is 18 minutes, and the hot pressing pressure is 15MPa.

[0051] Example 4

[0052] A cross-linking agent for rubber, whose raw materials include: 9g of polystyrene microspheres, 2g of methyl orthosilicate, 0.4g of copper sulfate, 1.3g of Span-20, 1.8g of vinyltrimethoxysilane, 0.03g of dibenzoyl peroxide, 5g of vinyl acetate, 1.3g of cobalt acetate, 0.08g of yttrium chloride, and 1.2g of graphene oxide.

[0053] The preparation method of the above-mentioned rubber cross-linking agent comprises the following steps:

[0054] S1. Add polystyrene microspheres, methyl orthosilicate and copper sulfate to 90 g of water, stir at 700 r / min for 18 min, add 220 g of petroleum ether and Span-20, stir at 9000 r / min for 7 min, adjust the pH value of the system to 8-9, perform ultrasonic treatment for 100 min, the ultrasonic frequency is 11 kHz, centrifuge at 4800 rpm for 3 min, wash, calcine at 480 ° C for 15 min, cool to room temperature, add 130 g of toluene and mix well to obtain activated silica;

[0055] S2, adding vinyl trimethoxysilane to 7g of deionized water and stirring for 25min, adding activated silica, condensing and refluxing at 82°C under nitrogen protection for 9h, adding dibenzoyl peroxide and stirring for 8min, adding vinyl acetate, continuing to reflux for 18h, centrifuging, washing, and vacuum drying to obtain grafted silica;

[0056] S3. Add the grafted silica to 10 g of deionized water, add cobalt acetate, yttrium chloride, and graphene oxide, and ultrasonically treat for 100 min at an ultrasonic frequency of 7 kHz and an ultrasonic temperature of 65° C., filter, wash, and vacuum dry at 58° C.

[0057] The method for using the above-mentioned rubber crosslinking agent comprises the following steps: feeding nitrile rubber, rubber crosslinking agent and antioxidant into a double-roll mixer at a mass ratio of 100:1.5:3.5, wherein the mixing temperature is 91°C and the mixing time is 18 minutes; and then feeding into a flat plate vulcanizer for hot pressing vulcanization molding, wherein the hot pressing temperature is 152°C, the hot pressing time is 22 minutes, and the hot pressing pressure is 13MPa.

[0058] Example 5

[0059] A cross-linking agent for rubber, whose raw materials include: 8g of polystyrene microspheres, 3g of methyl orthosilicate, 0.3g of copper sulfate, 1.5g of Span-20, 1.5g of vinyltrimethoxysilane, 0.05g of dibenzoyl peroxide, 4g of vinyl acetate, 1.5g of cobalt acetate, 0.05g of yttrium chloride and 1.5g of graphene oxide.

[0060] The preparation method of the above-mentioned rubber cross-linking agent comprises the following steps:

[0061] S1. Add polystyrene microspheres, methyl orthosilicate and copper sulfate to 80 g of water, stir at 800 r / min for 15 min, add 250 g of petroleum ether and Span-20, stir at 8000 r / min for 8 min, adjust the pH value of the system to 8-9, perform ultrasonic treatment for 90 min, the ultrasonic frequency is 12 kHz, centrifuge at 4500 rpm for 3.5 min, wash, calcine at 450 ° C for 20 min, cool to room temperature, add 120 g of toluene and mix well to obtain activated silica;

[0062] S2, adding vinyl trimethoxysilane to 8 g of deionized water and stirring for 20 min, adding activated silica, condensing and refluxing at 85 ° C for 8 h under nitrogen protection, adding dibenzoyl peroxide and stirring for 12 min, adding vinyl acetate, continuing to reflux for 15 h, centrifuging, washing, and vacuum drying to obtain grafted silica;

[0063] S3. Add the grafted silica to 12 g of deionized water, add cobalt acetate, yttrium chloride, and graphene oxide, and perform ultrasonic treatment for 90 min at an ultrasonic frequency of 9 kHz and an ultrasonic temperature of 60° C., filter, wash, and vacuum dry at 55° C.

[0064] The obtained rubber was subjected to electron microscopy scanning with a crosslinking agent, such as Figure 1 As shown, cobalt acetate, yttrium chloride, and graphene oxide are loaded on the surface of microspheres formed by copper oxide and silicon dioxide.

[0065] The method for using the above-mentioned rubber crosslinking agent comprises the following steps: feeding nitrile rubber, rubber crosslinking agent and antioxidant into a double-roll mixer at a mass ratio of 100:2:3 to mix into sheets, wherein the mixing temperature is 92°C and the mixing time is 15 minutes; and then feeding into a flat-plate vulcanizer for hot pressing vulcanization molding, wherein the hot pressing temperature is 155°C, the hot pressing time is 20 minutes, and the hot pressing pressure is 14MPa.

[0066] Comparative Example 1

[0067] Nitrile rubber, sulfur, carbon black and antioxidant were fed into a double-roll mixer in a mass ratio of 100:2:20:3 to form sheets, wherein the mixing temperature was 92°C and the mixing time was 15 min; and then the sheets were fed into a flat-plate vulcanizer for hot-pressing vulcanization molding, wherein the hot-pressing temperature was 155°C, the hot-pressing time was 20 min and the hot-pressing pressure was 14 MPa.

[0068] Comparative Example 2

[0069] A cross-linking agent for rubber, whose raw materials include: 8g of polystyrene microspheres, 3g of methyl orthosilicate, 0.3g of copper sulfate, 1.5g of Span-20, 1.5g of vinyltrimethoxysilane, 0.05g of dibenzoyl peroxide, 4g of vinyl acetate, 1.5g of cobalt acetate, 0.05g of yttrium chloride and 1.5g of graphene oxide.

[0070] The preparation method of the above-mentioned rubber cross-linking agent comprises the following steps:

[0071] S1. Add polystyrene microspheres and methyl orthosilicate to 80 g of water, stir at 800 r / min for 15 min, add 250 g of petroleum ether and Span-20, stir at 8000 r / min for 8 min, adjust the pH value of the system to 8-9, perform ultrasonic treatment for 90 min, the ultrasonic frequency is 12 kHz, centrifuge at 4500 rpm for 3.5 min, wash, calcine at 450 ° C for 20 min, cool to room temperature, add 120 g of toluene and mix well to obtain activated silica;

[0072] S2, adding vinyl trimethoxysilane to 8 g of deionized water and stirring for 20 min, adding activated silica, condensing and refluxing at 85 ° C for 8 h under nitrogen protection, adding dibenzoyl peroxide and stirring for 12 min, adding vinyl acetate, continuing to reflux for 15 h, centrifuging, washing, and vacuum drying to obtain grafted silica;

[0073] S3. Add the grafted silica to 12 g of deionized water, add cobalt acetate, copper sulfate, yttrium chloride, and graphene oxide, and ultrasonically treat for 90 min at an ultrasonic frequency of 9 kHz and an ultrasonic temperature of 60° C., filter, wash, and vacuum dry at 55° C.

[0074] The method for using the above-mentioned rubber crosslinking agent comprises the following steps: feeding nitrile rubber, rubber crosslinking agent and antioxidant into a double-roll mixer at a mass ratio of 100:2:3 to mix into sheets, wherein the mixing temperature is 92°C and the mixing time is 15 minutes; and then feeding into a flat-plate vulcanizer for hot pressing vulcanization molding, wherein the hot pressing temperature is 155°C, the hot pressing time is 20 minutes, and the hot pressing pressure is 14MPa.

[0075] Comparative Example 3

[0076] A cross-linking agent for rubber, whose raw materials include: 8g of polystyrene microspheres, 3g of methyl orthosilicate, 0.3g of copper sulfate, 1.5g of Span-20, 1.5g of vinyltrimethoxysilane, 0.05g of dibenzoyl peroxide, 4g of vinyl acetate, 1.5g of cobalt acetate, and 1.5g of graphene oxide.

[0077] The preparation method of the above-mentioned rubber cross-linking agent comprises the following steps:

[0078] S1. Add polystyrene microspheres, methyl orthosilicate and copper sulfate to 80 g of water, stir at 800 r / min for 15 min, add 250 g of petroleum ether and Span-20, stir at 8000 r / min for 8 min, adjust the pH value of the system to 8-9, perform ultrasonic treatment for 90 min, the ultrasonic frequency is 12 kHz, centrifuge at 4500 rpm for 3.5 min, wash, calcine at 450 ° C for 20 min, cool to room temperature, add 120 g of toluene and mix well to obtain activated silica;

[0079] S2, adding vinyl trimethoxysilane to 8 g of deionized water and stirring for 20 min, adding activated silica, condensing and refluxing at 85 ° C for 8 h under nitrogen protection, adding dibenzoyl peroxide and stirring for 12 min, adding vinyl acetate, continuing to reflux for 15 h, centrifuging, washing, and vacuum drying to obtain grafted silica;

[0080] S3. Add the grafted silica to 12 g of deionized water, add cobalt acetate and graphene oxide, and ultrasonically treat for 90 min at an ultrasonic frequency of 9 kHz and an ultrasonic temperature of 60° C., filter, wash, and vacuum dry at 55° C.

[0081] The method for using the above-mentioned rubber crosslinking agent comprises the following steps: feeding nitrile rubber, rubber crosslinking agent and antioxidant into a double-roll mixer at a mass ratio of 100:2:3 to mix into sheets, wherein the mixing temperature is 92°C and the mixing time is 15 minutes; and then feeding into a flat-plate vulcanizer for hot pressing vulcanization molding, wherein the hot pressing temperature is 155°C, the hot pressing time is 20 minutes, and the hot pressing pressure is 14MPa.

[0082] Comparative Example 4

[0083] A cross-linking agent for rubber, whose raw materials include: 3g of methyl orthosilicate, 0.3g of copper sulfate, 1.5g of Span-20, 1.5g of vinyltrimethoxysilane, 0.05g of dibenzoyl peroxide, 4g of vinyl acetate, 1.5g of cobalt acetate, 0.05g of yttrium chloride and 1.5g of graphene oxide.

[0084] The preparation method of the above-mentioned rubber cross-linking agent comprises the following steps:

[0085] S1. Add methyl orthosilicate and copper sulfate to 80 g of water, stir at 800 r / min for 15 min, add 250 g of petroleum ether and Span-20, stir at 8000 r / min for 8 min, adjust the pH value of the system to 8-9, perform ultrasonic treatment for 90 min, the ultrasonic frequency is 12 kHz, centrifuge at 4500 rpm for 3.5 min, wash, calcine at 450 ° C for 20 min, cool to room temperature, add 120 g of toluene and mix well to obtain activated silica;

[0086] S2, adding vinyl trimethoxysilane to 8 g of deionized water and stirring for 20 min, adding activated silica, condensing and refluxing at 85 ° C for 8 h under nitrogen protection, adding dibenzoyl peroxide and stirring for 12 min, adding vinyl acetate, continuing to reflux for 15 h, centrifuging, washing, and vacuum drying to obtain grafted silica;

[0087] S3. Add the grafted silica to 12 g of deionized water, add cobalt acetate, yttrium chloride, and graphene oxide, and perform ultrasonic treatment for 90 min at an ultrasonic frequency of 9 kHz and an ultrasonic temperature of 60° C., filter, wash, and vacuum dry at 55° C.

[0088] The method for using the above-mentioned rubber crosslinking agent comprises the following steps: feeding nitrile rubber, rubber crosslinking agent and antioxidant into a double-roll mixer at a mass ratio of 100:2:3 to mix into sheets, wherein the mixing temperature is 92°C and the mixing time is 15 minutes; and then feeding into a flat-plate vulcanizer for hot pressing vulcanization molding, wherein the hot pressing temperature is 155°C, the hot pressing time is 20 minutes, and the hot pressing pressure is 14MPa.

[0089] The tensile properties of the vulcanized nitrile rubber obtained in Example 5 and Comparative Examples 1-4 were tested with reference to GB / T 528-2009 "Determination of tensile stress-strain properties of vulcanized rubber or thermoplastic rubber". The sample size was 80×5×2mm, the tensile speed was 500mm / min, and the temperature was 25±1°C.

[0090] like Figure 2 As shown, under the same strain, the stress of the vulcanized nitrile rubber obtained in Example 5 is the highest, which is better than that of Comparative Examples 1-4 (P < 0.05), which proves that the vulcanized nitrile rubber obtained in Example 5 has good mechanical properties and can maintain good toughness.

[0091] The crosslink density of the vulcanized nitrile rubber obtained in Example 5 and Comparative Examples 1-4 was determined by the balanced solvent swelling method, with toluene as the balanced solvent. First, the initial weight m1 of the rubber was accurately weighed using an electronic analytical balance, and then placed in toluene. After the composite material was fully swollen for 72 hours at room temperature, the swollen rubber was taken out, and the toluene on the surface was dried with filter paper, and weighed to obtain m2. Finally, the sample was placed in an oven at 70°C and dried for 48 hours to constant weight to obtain m3; the crosslink density of each group of vulcanized nitrile rubber was calculated.

[0092]

[0093] Where γ is the crosslink density per unit volume of the composite material (mol / cm 3 ), V0 is the molar volume of toluene (V0 = 106.4 cm 3 / mol), χ is the interaction parameter between the rubber matrix and the solvent (for the nitrile rubber and toluene system, χ = 0.47), is the volume fraction of nitrile rubber in the swollen sample and can be determined according to the following formula:

[0094]

[0095] Where m1 is the mass of the original sample, ρ1 is the density of the original sample (nitrile rubber is 0.98 g / cm 3 ), m2-m3 and ρ2 are the mass and density of toluene respectively (ρ2=0.865g / cm 3 ).

[0096] like Figure 3 As shown, the crosslinking density of the vulcanized nitrile rubber obtained in Example 5 is the highest, which is better than that of Comparative Examples 1-4 (P < 0.05).

[0097] The samples obtained in Example 5 and Comparative Examples 1-4 were completely cut, immediately butted, and hot pressed at 150° C. for 30 min. The tensile strength after repair was tested, and the tensile strength repair rate was calculated to characterize the self-healing performance of the material.

[0098] Tensile strength repair rate = tensile strength after repair ÷ original tensile strength × 100%

[0099] like Figure 4 As shown, the tensile strength recovery rate of the vulcanized nitrile rubber obtained in Example 5 is the highest, which is better than that of Comparative Examples 1-4 (P < 0.01).

[0100] The applicant believes that the reason for the above results is that: the present invention uses methyl orthosilicate and copper sulfate to compound and deposit on the surface of polystyrene microspheres. After calcination, the surface of the formed hollow microsphere structure is vinylized and then combined with vinyl acetate. Not only can it have a good blending effect with nitrile rubber, but also can use the organic layer and graphene oxide therein to provide coordination crosslinking points. Subsequently, the transition metal and rare earth coordination effectively promote the formation of coordination crosslinks between chain rubber molecules, promote the rubber molecular structure from a chain structure to a network crosslinking structure, and effectively realize the vulcanization of nitrile rubber. At the same time, the obtained vulcanized rubber has good mechanical properties and the system maintains good toughness. The present invention loads transition metals and rare earths on the surface of the reinforcing material, which not only makes the transition metal distribution more uniform, but also greatly increases the specific surface area of ​​the transition metal. When used in the hot pressing and vulcanization forming process of nitrile rubber, it can not only form coordination bonds, but also effectively realize the coordination crosslinking of the nitrile rubber; and compared with traditional rubber, the present invention not only significantly increases the coordination efficiency, reduces the required metal salt content, and reduces the cost, but also cooperates with the reversible coordination bonds therein, and the system has a multiple network structure of reversible covalent bonds and non-covalent bonds, which can effectively realize the self-repair of crosslinking and reinforcement functions, and comprehensively improve the self-repair ability of nitrile rubber. At the same time, the repair process is simple and the repair efficiency is high, which is suitable for use as a new functional material.

[0101] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.

Claims

1. A crosslinking agent for rubber, characterized in that The raw materials include, by mass, 5-10 parts of polystyrene microspheres, 1-5 parts of methyl orthosilicate, 0.1-0.5 parts of copper sulfate, 1-2 parts of surfactant, 1-2 parts of vinyltrimethoxysilane, 0.01-0.1 parts of initiator, 2-6 parts of vinyl acetate, 1-2 parts of cobalt acetate, 0.01-0.1 parts of yttrium chloride and 1-2 parts of graphene oxide.

2. The rubber crosslinking agent according to claim 1, characterized in that: The surfactant was Span-20.

3. The rubber crosslinking agent according to claim 1, characterized in that: The initiator is dibenzoyl peroxide.

4. A method for preparing a crosslinking agent for rubber according to any one of claims 1 to 3, characterized in that: The steps include: S1. Add polystyrene microspheres, methyl orthosilicate and copper sulfate into water and stir for 10-20 min, add petroleum ether and surfactant and stir for 5-10 min, adjust the pH value of the system to 8-9, perform ultrasonic treatment for 1-2 h, centrifuge, wash, calcine at 400-500° C. for 10-30 min, cool to room temperature, add toluene and mix well to obtain activated silica; S2, adding vinyl trimethoxysilane to water and stirring for 10-30 minutes, adding activated silica, condensing and refluxing at 80-90°C under nitrogen protection for 5-10 hours, adding initiator and stirring for 5-20 minutes, adding vinyl acetate and continuing to reflux for 10-20 hours, centrifuging, washing, and vacuum drying to obtain grafted silica; S3. Add the grafted silica to deionized water, add cobalt acetate, yttrium chloride and graphene oxide, and ultrasonically treat for 1-2 hours, filter, wash and vacuum dry.

5. The method for preparing a cross-linking agent for rubber according to claim 4, characterized in that: In S1, the ultrasound frequency is 10-14kHz.

6. The method for preparing a cross-linking agent for rubber according to claim 4, characterized in that: In S1, the centrifugation speed is 4000-5000 rpm and the centrifugation time is 2-5 min.

7. The method for preparing a cross-linking agent for rubber according to claim 4, characterized in that: In S3, the ultrasonic frequency is 5-12 kHz and the ultrasonic temperature is 50-70°C.

8. The method for preparing a cross-linking agent for rubber according to claim 4, characterized in that: In S3, the vacuum drying temperature is 50-60°C.

9. A method for using the rubber crosslinking agent according to any one of claims 1 to 3, characterized in that: The method comprises the following steps: mixing nitrile rubber, the rubber crosslinking agent according to any one of claims 1 to 3 and an antioxidant into sheets, and hot pressing and vulcanizing the sheets at 150-160° C., wherein the hot pressing time is 15-25 minutes and the hot pressing pressure is 12-16 MPa.

10. The method for using the rubber crosslinking agent according to claim 9, characterized in that: The mass ratio of the nitrile rubber, the rubber crosslinking agent according to any one of claims 1 to 3, and the antioxidant is 100:1-3:2-4.

Citation Information

Patent Citations

  • Novel method for crosslinking acrylonitrile butadiene by supported transient metal

    CN101486800B

  • Preparation method of ceric sulfate coordinated and crosslinked nitrile elastomer

    CN102504294B

Cited By

  • Cross-linking agent, preparation method thereof and application of cross-linking agent in rubber preparation

    CN120966097A

  • A crosslinking agent, its preparation method and use in the preparation of rubber

    CN120966097B